Increasing the accuracy of electrostatic field strength measurement by using an improved differential transimpedance amplifier circuit - Povshenko, Oleksandr; Bazhenov, Viktor; Pazdrii, Olha; Bohdan, Halyna (Eastern-European Journal of Enterprise Technologies, 2023)
An electrostatic field mill (EFM) is widely used to measure the strength of electrostatic fields, the main drawback of which is the occurrence of large measurement errors (up to 15 % in the range from 0 to 1 kV/m). This paper examines the aspects of using transimpedance amplifiers (TIAs) for the tasks of converting the current received from the EFM sensor into voltage, which will make it possible to reduce the instrumental error and ensure the linearity of the atmospheric electrostatic field strength measurement. In the general case, for the functional circuits of the electrostatic field mill, which include a differential transimpedance amplifier, there is the use of two TIA circuits, which are connected in parallel. Despite the simplicity of implementation, such a configuration contains a number of disadvantages and is not optimal. In the paper, a comparative analysis of a typical circuit of a differential TIA and a circuit of an ungrounded differential transimpedance amplifier with zero voltage drop proposed by the authors is carried out. As a result of the analysis, it was established that the designed authentic circuit of the ungrounded differential transimpedance amplifier with zero voltage drop has better parameters of linearity and interference resistance, in contrast to the generally accepted one. The value of the signal-to-noise ratio for the proposed scheme improved by 42 % on average compared to the typical one. The main difference of the proposed scheme is that the stability of the amplification factor is ensured, the influence of the bias parameters of the operational amplifier is leveled, and the overall noise level is reduced. The use of the designed scheme of an ungrounded differential transimpedance amplifier with zero voltage drop could make it possible to increase the accuracy of the measurement of the electrostatic field strength